Macrophages in Recurrent Glioblastoma as a Prognostic Factor in the Synergistic System of the Tumor Microenvironment - Nicola Montemurro; Bhavya Pahwa; Anish Tayal; Anushruti Shukla; Manuel De Jesus Encarnacion; Issael Ramirez; Renat Nurmukhametov; Vishal Chavda; Antonella De Carlo (MDPI AG, 2023)
Glioblastoma (GBM) is a common and highly malignant primary tumor of the central nervous system in adults. Ever more recent papers are focusing on understanding the role of the tumor microenvironment (TME) in affecting tumorigenesis and the subsequent prognosis. We assessed the impact of macrophages in the TME on the prognosis in patients with recurrent GBM. A PubMed, MEDLINE and Scopus review was conducted to identify all studies dealing with macrophages in the GBM microenvironment from January 2016 to December 2022. Glioma-associated macrophages (GAMs) act critically in enhancing tumor progression and can alter drug resistance, promoting resistance to radiotherapy and establishing an immunosuppressive environment. M1 macrophages are characterized by increased secretion of proinflammatory cytokines, such as IL-1ß, tumor necrosis factor (TNF), IL-27, matrix metalloproteinase (MMPs), CCL2, and VEGF (vascular endothelial growth factor), IGF1, that can lead to the destruction of the tissue. In contrast, M2 is supposed to participate in immunosuppression and tumor progression, which is formed after being exposed to the macrophage M-CSF, IL-10, IL-35 and the transforming growth factor-ß (TGF-β). Because there is currently no standard of care in recurrent GBM, novel identified targeted therapies based on the complex signaling and interactions between the glioma stem cells (GSCs) and the TME, especially resident microglia and bone-marrow-derived macrophages, may be helpful in improving the overall survival of these patients in the near future.